EFL learners’ perceptions of their teachers’ explicit motivational strategies: A pilot questionnaire at two Hungarian universities - Naung, Han Htoo (Working Papers in Language Pedagogy, 2024)
Empirical studies focusing on the ways in which adult learners of English, especially students at tertiary level, may be motivated, can rarely be found in the EFL context though the teacher’s role is said to be important in creating and maintaining a motivating classroom setting (Kálmán, 2018). Therefore, the present study aims to investigate EFL learners’ perceptions concerning one particular motivating factor, namely their university EFL teachers’ use of explicit motivational strategies in the Hungarian higher education context. The data is collected from several universities in the country, using a 5-point Likert scale questionnaire survey. The results of the study show that Displaying appropriate teacher behaviours Creating a pleasant classroom climate, promoting learners’ self-confidence, and Recognising learners’ effort prove to be among the most important motivational dimensions among the learners. The strongest correlations appeared between the scales of Recognising learners’ effort and Promoting learners’ self-confidence, and between the Creating a pleasant classroom climate and Displaying appropriate teacher behaviour scales. This implies that if the participants are motivated by the teacher recognising and appreciating their effort, they are equally motivated by the teacher boosting learners’ self-confidence. It also indicates that appropriate teacher behaviour plays a vital role in establishing a supportive and pleasant classroom climate where learners feel comfortable and motivated.